UJI RADIONUKLIDA GIPSUM DENGAN METODE LASER INDUCED BREAKDOWN SPECTROSCOPY (LIBS) DAN PROTEKSI RADIASI DENGAN METODE JARAK - Wahyu, Mega; Sutapa, Ngurah; Balik Sudarsana, I Wayan (BULETIN FISIKA, 2016)
Research has been done to identify radionuklid which contain in gypsum with LIBS method and radiation protection with distance method. Test of gypsum radionuklid with LIBS method using 1 cm × 3 cm of gypsum and radiation protection with distance method using surveymeter with object gypsum board outside of room, plafond with gypsum matter inside of room and plafond with concrete matter inside of room.  Test of radionuklid with LIBS method indicate radionuklid elemen which contain in gypsum is Th (Thorium)  with rate intensity 456,5555 a.u and K (Kalium) with rate intensity 198,5555 a.u. From treshold decide for public people is 1 µSv/year can obtain save distance at midle of measurement position is 80 cm from gypsum board outside of room, 100 cm from plafond with gypsum matter inside of room and save for all distance from plafond with concrete matter inside of room. While, at corner of measurment save for all distance from gypsum board outside of room, plafond with gypsum matter inside of room and plafond with concrete matter inside of room.